2016
DOI: 10.1038/ncomms11802
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired sensitive and reversible mechanochromisms via strain-dependent cracks and folds

Abstract: A number of marine organisms use muscle-controlled surface structures to achieve rapid changes in colour and transparency with outstanding reversibility. Inspired by these display tactics, we develop analogous deformation-controlled surface-engineering approaches via strain-dependent cracks and folds to realize the following four mechanochromic devices: (1) transparency change mechanochromism (TCM), (2) luminescent mechanochromism (LM), (3) colour alteration mechanochromism (CAM) and (4) encryption mechanochro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
201
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 235 publications
(209 citation statements)
references
References 52 publications
0
201
0
Order By: Relevance
“…Inspired by nature, camouflage and wound healing are two important skills for organisms to overcome danger . For instance, the cephalopods have camouflage and wound healing bifunctions due to the muscle‐controlled color changes and the reconstruction of proteins, respectively (Figure a) . Herein, we report a new type of bioinspired healable mechanochromic (HMC) material that takes advantage of the multifunctional nature of biological systems.…”
Section: Figurementioning
confidence: 99%
“…Inspired by nature, camouflage and wound healing are two important skills for organisms to overcome danger . For instance, the cephalopods have camouflage and wound healing bifunctions due to the muscle‐controlled color changes and the reconstruction of proteins, respectively (Figure a) . Herein, we report a new type of bioinspired healable mechanochromic (HMC) material that takes advantage of the multifunctional nature of biological systems.…”
Section: Figurementioning
confidence: 99%
“…[8][9][10][11][12][13] The latter perspective has enabled engineering opportunities with self-adaptive/autonomous structures in low dimensions and has implications in many different contexts such as micro-/ nanofluidics, [14][15][16] flexible electronics, [17,18] adhesion, [19,20] organic solar cells, [21] tunable optics, [22][23][24] wettability, [25][26][27] and promising methods for surface patterning. [1,[28][29][30][31] While our scientific/technical understanding has advanced, there remains much to be explored about the control of instability morphology, and in particular how to configure instabilities, such as wrinkling and creasing, to desired patterns with selective distribution covering the surface and bespoke thresholds for the formation and evolution of instabilities.…”
Section: Doi: 101002/adfm201704228mentioning
confidence: 99%
“…[4][5][6][7][8][9] Inspired by the camouflage of cephalopods, there have been several studies of mimicking this ability. Light is reflected by the chromatophores, which consist of pigmentcontaining sacs.…”
mentioning
confidence: 99%
“…

of chromatophores, which are pigmented organs. [5][6][7][8][9] Sun et al reported a deformation-controlled method to harness mechano-chromisms by using optical design. By controlling the muscles attached to their surroundings, cephalopods such as squids can manipulate their skin's transparency.

…”
mentioning
confidence: 99%
See 1 more Smart Citation